Preferences in musical elements in ringtone selection: comparison between music and non-music undergraduate student - Loo, Fung Ying; Ling, Chia Lung; Loo, Fung Chiat; Tie, Fatt Hee (Asian Economic and Social Society, 2013)
Research into mobile phones is growing rapidly in terms of their usage, technology development, environmental and psychological effects, and so forth. The last decade has shown an increased interest in research into ringtones in identity, marketing, and environmental study. However, there is a lack of investigation into music elements, and preferences in ringtone still lack attention. The present study investigates the differences in ringtone preference by looking into various music metadata. This research took on a case study approach on undergraduate students from a local university. A survey was employed to investigate which musical elements were of most concern and which were left at the margin of attention when selecting a ringtone. Data collected were analyzed and the difference between preferences of music and non-music major undergraduate student in musical metadata was delineated.